Ajustes, seletividade e coordenação ótima entre dispositivos de proteção de redes de distribuição considerando suas características de tempo inverso por meio de algoritmos genéticos - SILVA, Dhonny Lima da (2018)
The genetic algorithm is presented to solve the problem of optimizing the coordination between protection devices in distribution networks. An objective function will developed to obtain the best coordination between such devices via its curves. Several curves will considered for the devices and the best one is selected by the genetic algorithm in order to achieve best coordination through the time-current curves. The study will explore the use of genetic algorithm as a method of artificial intelligence applied to the optimization of time of coordination between protection devices. It will be developed in Matlab 2010 a computer code that has as output characteristic curves of time-current of the devices included in the study of coordination and selectivity, seeking to provide at engineer, automatically, an optimized response and within the desired standards. Such objective is to investigate the potential application of genetic algorithms in the solve of problem of coordination and selectivity of the distribution network and at the same time, speed up and facilitate the work of engineers protection in distribution networks in the project phase, beyond facilitate studies of operation time discrimination of protection in existing facilities. This allows a wide variety of analyzes of coordination, sizing and selectivity of the protection system in a short time.